2010
DOI: 10.1080/08927011003629300
|View full text |Cite
|
Sign up to set email alerts
|

The effects of copper additives on the quantity and cell viability of adherentStaphylococcus epidermidisin silicone implants

Abstract: This in vitro study evaluated the antibacterial effect of copper additives in silicone implants. Specimens of a standard silicone material used in breast augmentation and modified copper-loaded silicone specimens were prepared and incubated in a Staphylococcus epidermidis suspension (2 h, 37 degrees C). After the quantification of adhering staphylococci using a biofluorescence assay (Resazurin), the viability of the adhering bacterial cells was quantified by live or dead cell labeling in combination with fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 45 publications
2
12
1
2
Order By: Relevance
“…Therefore, we applied fluorescence microscopy for directly monitoring bactericidal and anti-adhesive effects of copper-loaded substrata on the surface of the material. 31,39 Nevertheless, this study confirmed our previous findings, 26 i.e. no concentration-dependent effects could be found.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Therefore, we applied fluorescence microscopy for directly monitoring bactericidal and anti-adhesive effects of copper-loaded substrata on the surface of the material. 31,39 Nevertheless, this study confirmed our previous findings, 26 i.e. no concentration-dependent effects could be found.…”
Section: Discussionsupporting
confidence: 78%
“…47,48 After different aging durations, implants were incubated with a human isolate of S. epidermidis to imitate the natural contamination of silicone specimens for our in vitro study, a method that has proven to be valuable before. 26,49,50 Surprisingly, the findings of this study suggest that artificial aging does not affect R a and SFE of silicone specimens. The lack of change of surface characteristics due to artificial aging is rather striking as, for example, very resistant and hard-wearing dental materials have shown evident changes after the process of artificial aging.…”
Section: Discussioncontrasting
confidence: 38%
See 2 more Smart Citations
“…Silver,avery important antimicrobiala gent, was also incorporated by several researchers. [18d, 34] As ac omplementt os ilver, Gosau et al [35] workedw ith copperadditives.…”
Section: Incorporationmentioning
confidence: 99%